2012
DOI: 10.1186/2045-8118-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Active induction of experimental autoimmune encephalomyelitis by MOG35-55 peptide immunization is associated with differential responses in separate compartments of the choroid plexus

Abstract: BackgroundThere is increasing awareness that, aside from producing cerebrospinal fluid, the choroid plexus (CP) might be a key regulator of immune activity in the central nervous system (CNS) during neuroinflammation. Specifically, the CP has recently been posited to control entry of sentinel T cells into the uninflamed CNS during the early stages of neuroinflammatory diseases, like multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE). As the CP is compartmentalized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 73 publications
(87 reference statements)
4
34
0
Order By: Relevance
“…Thus the higher ANG II content in ChP4 may reflect different processing compartments or pools within ChP4. Indeed, it has been shown that ChP is compartmentalized into a stromal core with fenestrated capillaries and the tight-junction epithelium (43). Alternatively, there may be greater uptake and protected sequestration of ANG II from CSF or blood via AT 1 receptor internalization (22,40).…”
Section: Control Bmxmentioning
confidence: 98%
“…Thus the higher ANG II content in ChP4 may reflect different processing compartments or pools within ChP4. Indeed, it has been shown that ChP is compartmentalized into a stromal core with fenestrated capillaries and the tight-junction epithelium (43). Alternatively, there may be greater uptake and protected sequestration of ANG II from CSF or blood via AT 1 receptor internalization (22,40).…”
Section: Control Bmxmentioning
confidence: 98%
“…In most neuroinflammatory conditions, for example after TBI, chemokine expression at the CP increases gradually [7,105,106]. Moreover, an increase in chemokine expression was found after TBI in both the ipsilateral CP and the ipsilateral cerebral cortex that peaked at the same time after injury [7].…”
Section: Therapeutic Approaches and Caveatsmentioning
confidence: 94%
“…All animal protocols were in compliance with Animal Care and Use Guidelines of the University of Connecticut Health Center (Animal Welfare Assurance # A3471-01). Active EAE was induced as recently described (Murugesan et al, 2012), following a modification of the procedure ofSuen et al (1997). Subcutaneous flank injection of 300µg MOG35-55 peptide (MEVGWYRSPFSRVVHLYRNGK; synthesized by the Keck Biotechnology Resource Center at Yale University) in complete Freund’s adjuvant (Difco) containing 300µg M. tuberculosis was performed on day 0 (d0), and supplemented by intraperitoneal injections of 500ng pertussis toxin (List Biological) on d0 and d2.…”
Section: Methodsmentioning
confidence: 99%